The end of "Euro-romanticism" in Ukraine: The origins of anti-Western sentiments in the Presidential campaign - Volodymyr Mychajlovyč Kulyk (Stiftung Wissenschaft und Politik (SWP), 2009)
The beginning of the presidential campaign in Ukraine has produced foreign policy statements that differ markedly from the usual rhetoric of European integration. Except for the incumbent, Viktor Yushchenko, all prominent candidates display rather reserved attitudes towards the West in general and the European Union in particular. Moreover, in contrast to the earlier criticism of Yushchenko's 'Euro-romanticism', some candidates now go beyond presenting it as an established fact that the EU is not going to admit Ukraine and question the expediency of the very attempt. Although most candidates call for Ukraine's balanced relations with the West and Russia, disappointment with the former will lead to a greater dependence on the latter
Keywords: 320